Encouraging interviewees to say more and deception: The ghostwriter method. (22nd April 2019) - Leal, Sharon; Vrij, Aldert; Deeb, Haneen; Kamermans, Kevin
Abstract : Background: We examined a new method to encourage interviewees to say more, the ghostwriter method, and examined its effect on eliciting information and cues to deceit. Method: A total of 150 truth tellers and liars either told the truth about a trip they made in the last 12 months or pretended to have made such a trip. They were allocated to a Control condition, a 'Be detailed' condition in which they were encouraged to report even small details and a ghostwriter condition in which they were told to imagine talking to a ghostwriter. The dependent variables were details, complications, common knowledge details, self‐handicapping strategies, proportion of complications, plausibility, and verifiable sources. Results: The ghostwriter condition elicited more details and revealed in plausibility a stronger cue to deceit than the other two conditions. Conclusion: The ghostwriter method appears to be a promising tool for eliciting information and cues to deceit.